Translation Strategy in Matan Zubad's Translation Book by Muhammad Ali Baraqbah - Aji Saeful Ramdan; Yusroh Wahab (Universitas Muhammadiyah Gorontalo, 2022)
This study aims to describe the translation strategies used in the translated book of Matan Zubad by Muhammad Ali Baraqbah. This book is a translation from Arabic to Indonesian. The original title of this book is Matan Zubad. The theory used in this study is the theory of Mona Baker (2001). This research is a descriptive qualitative research with writing technique. Then analyzed with the translational equivalent method. The data obtained is 82 in the form of words, phrases and sentences from 100 poems studied. There are six strategies used in this book such as translation by a more general word (superordinate), translation by a more neutral/less expressive word, translation by cultural subtitution, Translation using a loan word or loan word plus explanation, translation by paraphrase using a related word, and translation by paraphrase using unrelated word. The word loan and explanation strategies are the most strategies often used by translators. This happens because this translated book comes from a book that studies fiqh where is many fiqh terms cannot be translated literally and must be using borrowing strategy. And because the language text source is a poem which is written using the Ijaz technique where the poem is expressed in a short word but its meaning is deep and broad. This makes the translator have to use description strategiy a lot so that the intent of the poetry can be conveyed and there is no misunderstanding.